European smart grid prospects, policies, and challenges. (January 2017) - IqtiyaniIlham, Nur; Hasanuzzaman, M.; Hosenuzzaman, M.
Abstract: A smart grid (SG) is developed to overcome grid congestion and to meet the demand for and sustain the supply of electricity. The European SG is supported by European Union (EU) policies and the joint EU Energy and Climate Package. This study reviews the prospects, progress, policies, and challenges faced by EU countries, electricity networks, and their relevant stakeholders. European SG prospects were initiated through the EU's Strategic Energy Technologies plan and continue with the strategic research agenda that has been road-mapped for 2007–2035. The EU, with its Directorates-General, agencies, and commissions, has established directives and policies to promote SG among member states. The factors that stimulate the innovation and implementation of SG require the need to generate electricity optimally (i.e., low greenhouse gas emission and renewable or sustainable source) and to secure its supply while ensuring reliability and quality. Despite the challenges, the European SG continues to develop and progress, fulfilling renewable energy targets and customer satisfaction and addressing environmental concerns.